USE OF COMPUTER-BASED EDUCATIONAL MEDIA TO IMPROVE THE LEARNING ABILITY OF INDUSTRIAL ENGINEERING STUDENTS IN CHEMISTRY - Tarigan, Sri Wahyuni (Jurnal Sistem Informasi dan Ilmu Komputer, 2023)
This study aims to determine differences in chemistry learning outcomes taught using computer-based media compared to conventional teaching on the Subject of Electrolyte and Non-Electrolyte Solutions. The research was conducted at Prima Indonesia University for the 2021/2022 Academic Year. The population of this study were all first- semester students consisting of two classes. A sample of 60 students, consisting of an experimental style and a control class, was given a different treatment, namely multimedia computer-based teaching with conventional media on the same subject. Based on data collection, the results obtained are that the experimental class has higher learning outcomes than the control class. Keywords: Computers, Electrolyte Solutions, Non-Electrolytes